SYNCHRONIZATION OF THE REVISION OF THE RTRW OF TEBING TINGGI CITY WITH THE REVISION OF THE RTRW OF NORTH SUMATRA PROVINCE CASE STUDY: SPACE PATTERN PLAN - Harry Kurniawan; Abdiyanto; Abdi Sugiarto (CV. RADJA PUBLIKA, 2024)
Spatial planning is arranged in a tiered hierarchy with spatial planning and regulation arranged through different levels, starting from the national level to the regional level. Each level has its own role and authority in preparing spatial plans which must be in harmony with the level above it. This hierarchy ensures that every spatial plan at the lower level must refer to and be in harmony with the spatial plan at the upper level, so as to create harmony and integration in the planning and use of space throughout Indonesia. The basic problems and conflicts in space utilization are the existence of significant challenges due to overlapping policies, regulations and geospatial information. The research is in Tebing Tinggi City, where in 2023 the Tebing Tinggi City Government and the North Sumatra Provincial Government will have revised the RTRW, so that a spatial study of the synchronization of the Provincial RTRW and City RTRW is needed. This research aims to provide an overview of the evaluation of the discrepancies in the revised spatial pattern plan of Tebing Tinggi City with the Revised RTRW of North Sumatra Province and to provide steps to resolve the discrepancies that occur which are useful as material for discussion and evaluation of the Revised RTRW of Tebing Tinggi City at the North Sumatra Province level. The research method uses a descriptive-qualitative approach with spatial exploration. Spatial analysis uses the ArcGIS 10.8 application to overlay which produces a comparison scheme. The matching scheme is then grouped into categories and typologies of